Expression pattern analysis of odorant‐binding proteins in the pea aphid Acyrthosiphon pisum. (29th April 2014) - De Biasio, Filomena; Riviello, Lea; Bruno, Daniele; Grimaldi, Annalisa; Congiu, Terenzio; Sun, Yu Feng; Falabella, Patrizia
Abstract: Odorant‐binding proteins (OBPs) are soluble proteins mediating chemoreception in insects. In previous research, we investigated the molecular mechanisms adopted by aphids to detect the alarm pheromone ( E )‐β‐farnesene and we found that the recognition of this and structurally related molecules is mediated by OBP3 and OBP7. Here, we show the differential expression patterns of 5 selected OBPs (OBP1, OBP3, OBP6, OBP7, OBP8) obtained performing quantitative RT‐PCR and immunolocalization experiments in different body parts of adults and in the 5 developmental instars, including winged and unwinged morphs, of the pea aphid Acyrthosiphon pisum . The results provide an overall picture that allows us to speculate on the relationship between the differential expression of OBPs and their putative function. The expression of OBP3, OBP6, and OBP7 in the antennal sensilla suggests a chemosensory function for these proteins, whereas the constant expression level of OBP8 in all instars could suggest a conserved role. Moreover, OBP1 and OBP3 are also expressed in nonsensory organs. A light and scanning electron microscopy study of sensilla on different body parts of aphid, in particular antennae, legs, mouthparts, and cornicles‐cauda, completes this research providing a guide to facilitate the mapping of OBP expression profiles.